MUSIC IN KÁLÁḆÀRÌ FUNERAL RITES (2013)
Duein-dibi-a nume (Funeral rites music) in Kalabari culture is a final honour for the dead and a status symbol for the living. It is performed for titled men, elders, members of Ekine cult and other socio-cultural clubs. Although duein-dibi-a nume occupies an important position in Kalabari culture, yet no musicological studies exist in terms of structure, significance and documentation especially as its traditional forms appear to be on the decline. This study, therefore, examined musical performances in funeral rites among the Kalabari of Rivers State, Nigeria. It categorised the different types of music, discussed their performance practices and also undertook their analyses. The study adopted the ethnographic research design. Data were collected from three Local Government Areas: Asari-Toru, Akuku-Toru and Degema that make up the Kalabari in Rivers State. Participant Observation method, In-depth-Interviews were conducted with twenty persons comprising the Amanyanabo (King) of Kalabari, and of Abalama, eight chiefs and elders, three chief drummers of Ekine cult, four Duein-dibi-a nume musicians, and three religious leaders reputed on Kalabari culture. Four Focus Group Discussion sessions were also held with Okoro fari and Okpokiri musicians, composers of Duein-duu-a nume and linguists from Bakana, Abonnema and Buguma. Data obtained were content analysed, while music recordings were transcribed into staff notation with the aid of the Finale music software for formal and structural analyses. Duein-dibi-a nume is performed by children and wives of the deceased, youths, women, elders, chiefs, and traditional musicians at different contexts in the community. It has four categories: Akwa nume (instrumental music), Ogbobe nume (choral music) with instrumental accompaniments, Duein-duu-a nume (acapella dirges and chants) and Seki nume (dance music). It is further grouped into ritual music: Okoro fari with fixed format performed for titled men; semi-ritual music: igira sara, boroma and amaboro used for entertainment as well as funeral ritual purposes; non-ritual music solely for entertainment: Okpokiri and Din krama ti (choreographed funeral dance) performances. Performance practices of Duein-dibi-a nume are event specific, contextual and rooted in Kalabari belief system. The melodies of Duein-dibi-a nume are made up of short phrases in solo, call and response, overlapping, mixed structural and presentation forms. Its rhythms are organised around simple duple, quadruple, and compound duple time. The text of the music serves psychological and spiritual purposes of encouraging the bereaved and facilitating the process for the dead of becoming an ancestor. Duein-dibi-a nume creates an enabling environment for communion in meeting spiritual and social needs. The serious decline in Duein-dibi-a nume was due to urbanisation, apathy on the part of the younger generation and also conversion of Kalabari people into other religions especially Christianity. The Duein-dibi-a nume performance, which manifests as instrumental and non-instrumental music, engenders socialisation and spiritual bonding in Kalabari celebration of life after life. Therefore, efforts must be directed at preserving this aspect of Kalabari culture through training of new generation of musicians by skillful and experienced ones particularly on traditional instruments.